ELAKSANAAN PEMASARAN JASA PENDIDIKAN DI MADRASAH IBTIDAYAH KURNIA ILAHI PULAU HARAPAN-BANYUASIN - Niswah, Choirun; Ibrahim, Ibrahim; Adinda, Diah (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
Abstract: This research is entitled "Implementation of Educational Services Marketing at Madrasah Ibtidayah Kurnia Divine Pulau Harapan Village". This study aims to determine the implementation of marketing of educational services in Madrasah Ibtidayah KurniaDivine Pulau Harapan Village. The type of research used in this research is descriptive qualitative research. The data that has been obtained and collected is through observation, interviews, and documentation. This type of research approach is descriptive qualitative. The techniques used in analyzing the data are as follows, namely data reduction, data presentation and conclusion drawing. To test the validity of the research data using data source triangulation, technical triangulation, and time triangulation. From the results of the research that has been carried out, it shows that to be able to find out how the implementation of marketing of educational services at Madrasah Ibtidayah Kurnia Ilahi Desa Pulau Harapan. Running effectively and efficiently. Providing the best service and marketing products by utilizing social media and outreach. Deepen religious knowledge such as worship and reading the Koran. Identify all objective facilities and obstacles. The supporting factors are human resources and costs. On the other hand, the inhibiting factors are product and promotion. In addition to these factors contained in this discussion there are also indicators which are one of the activities that take place in the marketing of educational services at madrasah ibtidayah kurnia ilahi devine pulau harapan village, namely education customer satisfaction, aducation customer loyalty, and finally, public opinion in image educational institutions. Keywords: Implemention, Service Marketing, Education